Empirical analysis of alternative pricing benchmarks for Islamic home financing product - Redzuan, Nur Harena; Kassim, Salina (2015)
Currently, major interest rates, such as the Base Lending Rate (BLR) and Kuala Lumpur Interbank Offered Rate (KLIBOR) are widely used as reference rates by the Islamic financial institutions to benchmark a broad range of financial products and contracts. This study aims to compare the viability of several alternative pricing mechanisms for the Islamic home financing products. By comparing the interest-based benchmark with the non-interest benchmark, this study attempts to highlight the sensitivity and fragility of the Islamic home financing product to financial market volatility. The study focuses on Malaysia as a case study and uses quarterly data frequency covering the period from 2009 to 2014. Specifically, the study compares lending rate and three alternative benchmark rate, namely Base Financing Rate (BFR), Housing Price Index (HPI) and KL Purpose-Build Office Rent Index (KL-PBO RI) with selected macroeconomic variables that could have related to the economic activities. Through the correlation analysis, the study finds that the non-interest benchmark has better relationships with selected macroeconomic variables compared to the interest-based benchmarks. It shows that these alternative benchmarks have the connection to the economic movements that lead to the stability of the non-interest financing instruments. The findings of this study would provide important insights into the viability of house price index and rental index as the alternatives to the benchmark of the equity financing home financing product. This study contributes to the empirical evidence for the feasibility of adopting the interest-free benchmark to price Islamic home financing product.